2017
DOI: 10.1016/j.jvs.2017.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities after infrainguinal bypass surgery in hemodialysis patients

Abstract: This large study confirms the presence of multidirectional racial disparities in graft durability, limb salvage, and mortality after IBS in HD patients. Black patients had lower graft patency and higher limb loss than white and Hispanic patients, whereas perioperative and long-term mortality was higher in white patients. These results should inform further granular root cause analyses and subsequent action to eliminate these disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Regional variation has been shown to contribute to perioperative outcome disparities seen between black and white patients in the VQI. 20 Black and Hispanic patients have been more likely to have limb loss and less likely to maintain bypass patency; 49 with increased rates of limb loss persisting in black patients even when socioeconomic status was matched to white counterparts 21 though black and Hispanic patients have been shown to have lower rates of long-term mortality in comparison to white counterparts. 20,22 Amid the known superior patency of vein grafts compared to prosthetic conduit in IIB, 10 vein conduit utilization if feasible and of adequate size is an element of optimal care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regional variation has been shown to contribute to perioperative outcome disparities seen between black and white patients in the VQI. 20 Black and Hispanic patients have been more likely to have limb loss and less likely to maintain bypass patency; 49 with increased rates of limb loss persisting in black patients even when socioeconomic status was matched to white counterparts 21 though black and Hispanic patients have been shown to have lower rates of long-term mortality in comparison to white counterparts. 20,22 Amid the known superior patency of vein grafts compared to prosthetic conduit in IIB, 10 vein conduit utilization if feasible and of adequate size is an element of optimal care.…”
Section: Discussionmentioning
confidence: 99%
“…3 Racial disparities with regard to outcomes following IIB have previously been noted, with black and Hispanic patients more likely to have limb loss and less likely to maintain bypass patency. [4][5][6][7][8][9] Vein grafts have superior patency compared to prosthetic conduit for IIB. 10 The choice of conduit use (vein versus prosthetic) is often made at a surgeon level due to existing patient factors (such as anatomy and prior intervention history) and it is unknown whether there is an association of race with conduit choice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The current study revealed higher loss of graft patency and limb loss among black women compared with white women, thus attracting the need to explore the practice-and tissue-level drivers of gender and racial disparities in outcomes. 21 Most of the limitations of our study are inherent to retrospective design and use of an administrative database. We cannot account for severity of disease, medication use, vein type or size, and prior or concurrent endovascular interventions.…”
Section: Discussionmentioning
confidence: 99%
“…While a number of studies have demonstrated poor outcomes of lower extremity revascularization in patients with ESRD, little is known about results in patients with renal transplants . Previous reports have involved small cohorts and have often grouped together transplant and dialysis patients.…”
Section: Introductionmentioning
confidence: 99%